Immune paradigm and immunosuppressive dominance in the pathogenesis of major diseases of the modern man - V. A. Kozlov (Бюллетень сибирской медицины, 2019)
The article discusses the determining role of immunopathogenesis of the main diseases of the modern man (cancer, atherosclerosis, autoimmune, allergic and infectious diseases). In this regard, the concept of «immune paradigm» is introduced. There is evidence that any pathology is based on the classical immune response to the antigen, whether auto- or xenoantigen, with all stages of its development and parallel changes in the state of immune tolerance: its breakdown in cases of autoimmune and allergic diseases and atherosclerosis; its establishment in cases of cancer and infectious diseases. In the meantime, it is emphasized that the immunopathogenesis is based on insufficient or increased function of immunocompetent regulatory cells with suppressive activity. Here the concept of «immunosuppressive dominant» is introduced. Finally, we discuss the need for fundamental changes in treatment of these diseases, with a focus on molecular and cellular immunotherapy methods and development of integrated approaches to their application.